Effects of Inoculum Amount, Initial pH, and Nicotine Load on the Set-Up of Bioaugmented System with Pseudomonas Sp. HF-1 to Treat Tobacco Wastewater - Kun Zhang; Hong-zhen He; Dong-sheng Shen; Xin Zheng; Zhou Zhou; Xian-jun Tao; Mei-zhen Wang (Journal of Chemistry)
This study evaluated and optimized the influence of inoculum amount, initial pH, and nicotine load on the construction of Pseudomonas sp. HF-1 bioaugmented system for tobacco wastewater treatment. The results demonstrated that the optimum condition for the set-up of strain HF-1 bioaugmented system was 1.10 mg/g (dry weight of strain HF-1/dry weight of activated sludge) of inoculum amount, initial pH 7.0, and 250–1000 mg/L nicotine load. Higher than 1.10 mg/g could lead to noncolonization of strain HF-1 in activated sludge and failure of set-up of this bioaugmented system. Higher than pH 8.0 could restrain the colonization of strain HF-1 in activated sludge. Even though strain HF-1 colonizes in the activated sludge when pH was above 8.0, the removal of nicotine and total organic carbon (TOC) was suppressed due to low activities of bacteria in the activated sludge. Nicotine load did not show inhibition effect on set-up of bioaugmented system, but the ability of TOC removal was restrained when the nicotine load was above 1000 mg/L. This work could offer vital parameters for the set-up of bioaugmented system to treat tobacco wastewater in engineering.